Interaction Between High Soil Zinc Level and Silicon Application Methods in Maize Plants - Rodrigues da Silva, Ana Paula [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Deus, Angélica Cristina Fernandes [UNESP]; Büll, Leonardo Theodoro [UNESP] (Springer Nature, 2023)
Propose: The present study proposes to examine the efficiency of Si application methods and their effect in intermediate and high levels of Zn in maize plants. Methods: Two experiments were carried out: one in sandy soil and another in clay soil. The Si rates were applied in the planting furrow or in the total area, individually or combined with Zn at intermediate or high levels. Evaluations were performed in the plant (Zn and Si contents and accumulation; plant height; leaf area; SPAD index; and shoot, leaf, stem, and root dry weights) and in the soil (Zn and Si contents and pH). Results: The treatments individually or in combination with Zn at intermediate or high levels influenced in sandy and clay soil for the variables plant height, leaf area, shoot and leaf dry weights, shoot Zn and Si and accumulation and Zn and Si soil contents. And still, in sandy soil also influenced in stem and root dry weights. The Si application methods influenced in clay soil on plant height, shoot Zn accumulation, soil Si, shoot and dry weights of leaves, stem, and root. However, in sandy soil, Si application methods influenced plant height and soil pH. Conclusions: In sandy soil, the combination of a lower dose of Si with a higher rate of Zn resulted in increased concentrations of Zn in the plant. The Si application methods decreased of Zn content in soil of clay texture and shoot Zn accumulation in sandy soil. The Si application methods had a greater influence on the parameters evaluated in sandy soil.
Keywords: Beneficial element; Silicate; Trace elements; Tropical soil